2010
DOI: 10.22358/jafs/66298/2010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium butyrate on calf growth and serum level of β-hydroxybutyric acid

Abstract: The experiment was carried out on 40 Polish Black-and-White HF bull calves (52-87% of HF blood) aged from 9 and 12 days at the beginning of the experiment to 90 days at its end. From the beginning of the trial the calves were offered restricted liquid feed to 56 days of age and concentrates ad libitum according to Iz-PIB-INRA recommendations. The concentrates were without sodium butyrate (control group, C), or with 1% Na-butyrate (group B1), 3% Na-butyrate (group B3) and 0.3% Na-butyrate (group B0.3), and incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
8
24
0
Order By: Relevance
“…The dietary level of butyrate did not cause changes in the serum ß-hydroxybutyrate concentration in calves (Slusarczyk et al 2010) and butyrate disappears from the upper GIT (mainly in the stomach). It is thought to be metabolized in the GIT wall (and/or in the liver) because it is not found in the peripheral blood (Manzanilla et al 2006, 2010a.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The dietary level of butyrate did not cause changes in the serum ß-hydroxybutyrate concentration in calves (Slusarczyk et al 2010) and butyrate disappears from the upper GIT (mainly in the stomach). It is thought to be metabolized in the GIT wall (and/or in the liver) because it is not found in the peripheral blood (Manzanilla et al 2006, 2010a.…”
Section: Introductionmentioning
confidence: 81%
“…The reported experiments were conducted in very young calves (%1 . 5 months) which ingested MF and starter diet from 3 days after birth, whereas the measurements for other studies were obtained in milk-fed (Guilloteau et al , 2010b or in weaned (Slusarczyk et al 2010) calves aged at least 2 months. In fact, it was demonstrated, in different species, that butyrate must be ingested immediately after birth, but the growth performances were observed later in life , 2010b, Le Gall et al 2009.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We manually stirred the mixture to dissolve the SB before feeding. The doses of SB supplementation were adjusted from the work of Slusarczyk et al who fed calves SB at 2.2 to 22 grams per day [22].…”
Section: Animals Treatments and Managementmentioning
confidence: 99%
“…However, Wanat et al [21] reported con icting results that even at 0.3%, 0.6%, and 0.9 % of DM, microencapsulated SB added to starter mixture reduced the growth performance in calves, including linear decreases in ADG and BW in a dose-dependent manner. Slusarczyk et al [22] showed that SB was well tolerated and it improved growth performance when supplemented at 1-3% of DM mixed either in MR before weaning (56 days of age) or in concentrates fed ad libitum post-weaning (until the end of the experiment at 90 days of age). However, it was found that SB supplementation at 3% of DM reduced feed intake despite a positive effect on calf growth and nutrient utilization.…”
Section: Introductionmentioning
confidence: 99%